The course of schizophrenia in the light of modern follow-up studies: the ABC and WHO studies - Häfner, Heinz; Heiden, Wolfram an der (European archives of psychiatry and clinical neuroscience, 1999)
In schizophrenia most of the social consequences emerge in the prodromal phase of the illness and before treatment is initiated. Further course is determined by the level of social development at illness onset and by age- and sex-related illness behavior. Despite the sex difference in age at onset the disease process seems to be the same in both sexes, since social course in men and women converges in the long run. Although great variation in outcome between the patients is to be observed at each cross-section, the medium and long-term symptom-related course of schizophrenia shows a high degree of stability at the individual level.